EFFECTS OF CIPROFLOXACIN AND ZINC CHLORIDE IN ADULT ALBINO RAT AND PRE-NATAL CONCEPTUS - Channa, Muhammad Aslam; Ashfaq, Muhammad; Jokhio, Abdul Lateef; Khan, Muhammad Zaheer; Sahito, Mir Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Administration of quinolone therapy is controversial during growing age as stated by earlier authors. The flouroquinolones are currently not indicated for young children because of arthropathy and adverse effect as new born shown by studies. However the effects of ciprofloxacin and ZnCl2 on prenatal conceptus have remained undocumented. The present study was designed to compare the effects on conceptus after maternal ingestion of ciprofloxacin and ZnCl2 using Wastar albino rats. Methods: Ciprofloxacin and ZnCl2 was administrated to pregnant female albino rats. Ciprofloxacin with a dose of 20 mg/Kg bodyweight and ZnCl2 120 µg/100 gm bodyweight two times therapeutic dose for 10 days (from day 8-18 of pregnancy). Each animal was weighted on day 1, day 8 and day 18 of pregnancy. Abortion resulted on day 18th of pregnancy. Each group of pregnant animals were sacrificed on day 18 of gestation by over dose of either anaesthesia, abdomen opened, uterus and both cornua containing conceptus identified, removed, there weight recorded, crown rump length was measured and was compared with similar value of control animals. The results were statistically analysed to find out the significance. Results: The ciprofloxacin induces a mordanting effect as obviated by increased basophilia. Our study reveals that ciprofloxacin administered in maternal, decreased maternal body weight to 38.4±0.9 gm. However simultaneous ZnCl2 maintained the body weight to 41.4±0.7 gm, while ZnCl2 increased the body weight to 46.5±2.25 gm. The body weight and Crown Rump length (CR Length) in conceptus decreased by 4.52±0.10 gm and 3.06±0.09 Cm respectively. That ciprofloxacin and ZnCl2 administration maintained the body weight and CR length by 5.46±0.09 gm and 3.79±0.13 Cm respectively. That ZnCl2 administration increased the body weight and CR length by 6.71±0.05 gm and 4.15±0.08 Cm respectively. Conclusion: Prenatal administration of Ciprofloxacin caused reduction in growth rate and CR length, and ZnCl2 maintained body weight and CR length and growth of the rat conceptus. Keywords: Ciprofloxacin, ZnCl2, body weight, crown rump length, conceptus